miR-193b, miR-671 and TREM-1 as molecular prognostic biomarkers in leishmaniasis caused by L. braziliensis - Noronha, M. A. P. L. de (2023)
Universidade Federal da Bahia. Salvador, BA, Brasil / Fundação Oswaldo Cruz. Instituto Gonçalo Moniz. Salvador, BA, Brasil.